1963
DOI: 10.1128/jb.85.4.732-741.1963
|View full text |Cite
|
Sign up to set email alerts
|

CHARACTERISTICS OF A STRAIN OFSTAPHYLOCOCCUS AUREUSGROWN IN VIVO AND IN VITRO

Abstract: Characteristics of a strain of Staphylococcus aureus grown in vivo and in vitro. J. Bacteriol. 85:732-741. 1963.-A comparative survey was conducted on the characteristics of a strain of Staphylococcus aureus after it had been grown in vitro (VSB) and after it had been collected from the peritoneal exudate of an infected guinea pig (GSB). Both VSB and GSB strains gave the same results when studied in an extensive series of tests, including bound and soluble coagulases, bacteriophage type, antibioticsensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Ivler (1965) reported that virulent staphylococci consumed oxygen at a more rapid rate than did avirulent staphylococci. Similar results were reported by Beining and Kennedy (1963) who demonstrated that when virulence was increased by animal passage the respiratory activity of the staphylococcal cells increased. The metabolic energy obtained through increased respiratory activity may be utilized for the synthesis, repair of in tissue extracts of normal and of 0, 1 and 4 days severe bruises (A) and slight bruises (8).…”
Section: Respirationsupporting
confidence: 89%
“…Ivler (1965) reported that virulent staphylococci consumed oxygen at a more rapid rate than did avirulent staphylococci. Similar results were reported by Beining and Kennedy (1963) who demonstrated that when virulence was increased by animal passage the respiratory activity of the staphylococcal cells increased. The metabolic energy obtained through increased respiratory activity may be utilized for the synthesis, repair of in tissue extracts of normal and of 0, 1 and 4 days severe bruises (A) and slight bruises (8).…”
Section: Respirationsupporting
confidence: 89%
“…Mycobacterium isolated from infected mouse tissues exhibit reduced oxidation capacity because of deficiency of cytochromes (6,13). Staphylococcus aureus grown in vivo, on the contrary, shows a higher state of oxidation activity and produces far more hemolysin, leucocidin, and tissue-attacking enzymes (1,4). Most pathogenic fungi show dual aspects of the morphology of fungi in their saprophytic and parasitic states (8).…”
mentioning
confidence: 99%
“…Woods and Foster (116) have discussed the almost complete lack of knowledge of bacterial metabolism in vivo and the reasons why it probably differs from metabolism in vitro. The metabolism of Bacillus anthracis in vivo is different from that in vitro (110), and, although observations in vitro on the metabolism of bacteria isolated directly from infected animals will not detect all aspects of metabolism in vivo (116), such observations on tubercle bacilli (15,69,107), plague bacilli (40), staphylococci (12), and streptococci (44) indicated marked differences in metabolism between these organisms and those grown in vitro. These observations should be extended, because knowledge of microbial metabolism in vivo might be important not only in studies of virulence but for the design of new antibacterial drugs.…”
Section: Growth and Multiplication In Vivomentioning
confidence: 99%